Systematic review with meta‐analysis: endoscopic and histologic placebo rates in induction and maintenance trials of ulcerative colitis. Issue 12 (25th April 2018) - Ma, C.; Guizzetti, L.; Panaccione, R.; Fedorak, R. N.; Pai, R. K.; Parker, C. E.; Nguyen, T. M.; Khanna, R.; Vande Casteele, N.; D'Haens, G.; Sandborn, W. J.; Feagan, B. G.; et al.
Summary: Background: Regulatory requirements for claims of mucosal healing in ulcerative colitis (UC) will require demonstration of both endoscopic and histologic healing. Quantifying these rates is essential for future drug development. Aims: To meta‐analyse endoscopic and histologic placebo response and remission rates in UC randomised controlled trials (RCTs) and identify factors influencing these rates. Methods: MEDLINE, EMBASE and the Cochrane Library were searched from inception to March 2017 for placebo‐controlled trials of pharmacological interventions for UC. Endoscopic and histologic placebo rates were pooled by random effects. Mixed effects univariable and multivariable meta‐regression was used to evaluate the influence of patient, intervention and trial‐related study‐level covariates on these rates. Results: Fifty‐six induction (placebo n = 4171) and 8 maintenance trials (placebo n = 1011) were included. Pooled placebo endoscopic remission and response rates for induction trials were 23% [95 confidence interval (CI) 19‐28%] and 35% [95% CI 27‐42%] respectively, and 20% [95% CI 16‐24%] for maintenance of remission. The pooled histologic placebo remission rate was 14% [95% CI 8‐22%] for induction trials. High heterogeneity was observed for all outcomes ( I 2 56.2%‐88.3%). On multivariable meta‐regression, central endoscopy reading was associated with significantly lower endoscopic placebo remission rates (16% vs 25%; OR = 0.52, [95% CI 0.29‐0.92], P = 0.03). On univariable meta‐regression, higher histologic placebo remission was associated with concomitant corticosteroids (OR = 1.17 [95% CI 1.08‐1.26], P < 0.0001, per 10% increase in corticosteroid use). Conclusions: Placebo endoscopic and histologic rates range from 14% to 35% in UC RCTs but are highly heterogeneous. Outcome standardisation may reduce heterogeneity and is needed in this field.